2019
DOI: 10.1055/s-0039-1692965
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Executive Function in Developmental Stuttering

Abstract: Developmental stuttering is a complex disorder and children who stutter form a heterogeneous group. Most contemporary researchers would agree that multiple factors, including those associated with linguistic, motor, sensory, and emotional processes, are likely involved in its development and/or maintenance. There is growing evidence, however, that cognitive processes also play a role. In this article, we briefly review behavioral and parent-report studies of executive function in children who stutter, the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 68 publications
(102 reference statements)
2
20
0
3
Order By: Relevance
“…Both parent reports and cognitive assessments have been used to evaluate EF in CWS and they suggest EF components are depressed in this population [ 6 for a review see 80 ]. WM underpins the ability to store and manipulate relevant information during complex tasks, and is proposed to be critical for fluency [ 64 , 81 83 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both parent reports and cognitive assessments have been used to evaluate EF in CWS and they suggest EF components are depressed in this population [ 6 for a review see 80 ]. WM underpins the ability to store and manipulate relevant information during complex tasks, and is proposed to be critical for fluency [ 64 , 81 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…Executive attention oversees available resources for cognitive processes including speech production [ 98 , 99 ]. Both direct and indirect measurements suggest greater difficulty in managing attention for CWS compared to CWNS [for a review see 80 ]. Parent- and teacher-reports point to lower attentional flexibility and sustained attention in CWS [ 100 102 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific analysis of the research problem has shown that many authors value the role of functional training with stutterers. The latter allows the appropriate verbal behavior to be formed and use of word as communication mean in different social environment (Anderson & Ofoe, 2019;Missulovin, 1988). According to authors these interventions must first be organized at home, but in many cases families are not aware about the methods and tools that can be used while organizing this intervention in practice.…”
Section: Procedures and Resultsmentioning
confidence: 99%
“…The construct of executive function was chosen because it has been linked to childhood stuttering (Ntourou et al, 2018 ; Anderson and Ofoe, 2019 ). Executive function refers to a suite of higher-order cognitive processes, particularly attention, working memory, and inhibitory control, that are implicated in planning and goal-directed behavior (Miyake et al, 2000 ).…”
Section: Emotional Reactivity and Regulation In Children Who Stuttermentioning
confidence: 99%